The Effect of Different Doses of Intraamniotic Digoxin on the Timing of Fetal Demise in Second Trimester Medical Abortions - Aynaoglu Yildiz, Gulsah; Al, Ragip Atakan (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVES: The World Health Organization recommends feticide for termination of pregnancy after 20 weeks of gestation, and the Royal College of Obstetricians & Gynecologists after 21 weeks and 6 days. Digoxin is a commonly used feticidal agent. This retrospective study aimed to show the effect of different doses of digoxin on the timing of fetal demise when used for feticide. STUDY DESIGN: Our retrospective cohort study included 57 patients who underwent feticide by routine intra-amniotic digoxin 0.75 mg or 1 mg between 2016 and 2018 at the Ataturk University Medical Faculty Research Hospital. The patients were administered undiluted digoxin 0.75 mg (3 ccs) or 1 mg (4 ccs) with a 20-gauge spinal needle inserted through the amniotic membrane. After digoxin administration, the fetal heartbeat was monitored every hour by ultrasound, and recorded. RESULTS: In this retrospective study, we reviewed the data of 61 patients who underwent feticide by intra-amniotic digoxin 0.75 mg and 1 mg. Digoxin 3 ccs (n=23) and digoxin 4 ccs (n=34). The two groups were not significantly different in terms of age, gestational week, and termination indications. We reviewed the medical records of all subjects and noted any side effects. CONCLUSIONS: In our study, we investigated the effect of different doses of intra-amniotic digoxin on the fetal demise in accordance with the literature. Despite our small sample size, we conclude that a higher dose of digoxin will reduce the time to asystole and minimize the mental burden of the procedure on the patient.